ANALISIS STRATEGI MARKETING MIX SYARIAH DALAM PENINGKATAN VOLUME PENJUALAN : Studi Kasus Rumah Makan Ayam Kremes Arema Di Kecamatan Rimbo Bujang (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the sharia marketing mix strategy, inhibiting factors and efforts to increase sales of Kremes Arema Chicken Restaurant in Rimbo Bujang District. This study used qualitative methods and the sample of this study was the owner of Kremes Arema Chicken Restaurant. Data collection through observation, interviews, and documentation. The conclusions show that: (1) The sharia marketing mix strategy has not been carried out optimally (2) Production inhibiting factors include; the amount of money available for promotion, the nature of the market, the nature of the product and the product life cycle (3) The efforts made by Kremes Arema Chicken Restaurant in increasing sales include; Find new customers, respond quickly to customers, add new employees, and have special access for buyers to choose products safely and comfortably.